Participatory democracy and climate governance in Brazil: theoretical foundations and local experience (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
This study analyzes social participation in the environmental field and its correlation with multilevel governance. It uses the experience of the São Carlos Participatory Citizens Forum to demonstrate the potential of interaction between public authorities and civil society.(Received: September 2025 | Accepted: October 2025)
Keywords: Participatory Democracy; Climate Governance; Social Participation; São Carlos; Local Management